327 COMPARISON OF SHORT-, INTERMEDIATE-, AND LONG-ACTING INSULIN SECRETAGOGUES IN TYPE 2 DIABETES. (1st January 2006) - de Serna, Gonzalez D.; Robinson, I.; Martin, P.; Burge, M. R.; Schade, D. S.
Abstract : Purpose: There is controversy regarding the optimal choice of an insulin secretagogue to prevent hyperglycemia during the postprandial period. Therefore, we compared the effect of a short- (nateglinide), intermediate- (glyburide), and long-acting (extended-release glipizide) insulin secretagogue versus placebo during the 6-hour postprandial period. Methods: We conducted a single-blind, randomized, crossover study in six non-insulin-requiring subjects with type 2 diabetes. Each subject completed four arms: placebo, nateglinide, glyburide, and extended-release glipizide. Subjects took the study medication for 7 days prior to being admitted to the General Clinical Research Center for study. The study included administration of study medication followed by a test meal. Frequent blood samples were drawn for glucose, insulin, and C-peptide before and for 6 hours after the test meal. Results: As expected, glucose levels were higher throughout the study in the placebo arm ( p < .05). However, there were no statistical differences in glucose, insulin, or C-peptide levels between short-, intermediate-, and long-acting insulin secretagogues (p > .05). The incidence of hypoglycemia events was greatest with glyburide. The calculated cost per month of each medication at its recommended dose was: nateglinide ($105) > glyburide ($24) > extended-release glipizide ($14). Conclusions: Our results demonstrate that during the postprandial period none of the insulin secretagogues studied showed significantly better glucose, insulin, or C-peptide response. Thus, when choosing an insulin secretagogue, health care providers should base their decisions on cost and convenience of use.